Didactic Symbol of Visual Images in EFL Textbook: Multi-modal Critical Discourse Analysis - Titin Purwaningtyas (Jurnal Pedagogy, 2020)
The textbook plays an essential role for students in the teaching and learning process. Imagery, combined with texts in the textbook, makes subjects easy to understand. Images are generally used to convey things we can't tell in the text. Visual images help students make sense of output and input around them. This study investigates the representation of the visual image in the EFL textbook proposed by using a multimodal discourse analysis method. The researcher used the framework from Kress van Leeuwen. Information from all visual images consist of 158 images in the Indonesian EFL textbook is collected as the data in this study. The results showed that females (70%) portions were more commonly portrayed than males ( 30%). In terms of social roles, females have the same proportion of occupations as males. In terms of image appearance, the foreign and Indonesian cultures portrayed to show the tolerance culture. This study aims to explore the meaning of the integrated use of semiotic resources, such as visual image representation in the textbook. The researcher expected students and teachers as textbook users could increase their understanding with the subject of teaching and learning by interpreting the visual images effectively. This study recommends to the textbook user that visual images appearances can strengthen the text or written material in the textbook. Also, it suggests textbook publishers be more concerned and synchronize between the written content and the visual representation portrayed not to occur misinterpretation among the textbook users.